SPECTRUM OF ORAL AND MAXILLOFACIAL SURGERY PATIENTS SEEN AT TRIAGE WITH SUBSEQUENT EMERGENCY TREATMENT PROVIDED – A CLINICAL STUDY AT SMBBIT - KUMAR , S; KATPAR , S; LUHANA , D; AMAN , A; KUMAR , M; KESWANI , S (Biological and Clinical Sciences Research Journal, 2024)
Oral and maxillofacial injuries constitute a significant portion of trauma cases in emergency departments, often resulting in life-threatening complications and sometimes death. Effective triage is crucial for prioritizing care, especially in resource-limited settings. Despite the importance of standard protocols, many institutions lack uniform guidelines for managing these complex injuries, which can lead to adverse patient outcomes. Objectives: To explore the clinical presentation patterns of oral and maxillofacial trauma patients at triage, focusing on injury types and patient demographics while documenting initial emergency interventions administered. Methods: This descriptive cross-sectional study was conducted at SMBBIT over six months, involving patients presenting with OMFS Trauma sustained at Emergency Room. Data were collected using a pre-designed pro forma and analyzed using SPSS software for descriptive statistics. Results: A total of 73 patients were included, predominantly male (84.94%), with a mean age of 35.2 years. Road traffic accidents were the leading cause of injury (68.5%). Most patients were self-referred (37%), and 82.2% had no significant co-morbidities. Imaging revealed comminuted pan-facial fractures (37.5%) as the most common diagnosis. Following triage assessment, 80.8% required hospitalization, with 32.2% undergoing immediate surgical interventions, including open reduction internal fixation, closed reduction and soft tissue closure. Conclusion: This study underscores the importance of effective triage in managing oral and maxillofacial surgical patients, particularly in polytrauma cases, with a focus on a multidisciplinary team (MDT) approach. Our findings suggest that incorporating oral and maxillofacial surgical emergency care into triage protocols and resource allocation can improve care quality and reduce patients’ complications. Inclusion of oral and maxillofacial surgeons in Emergency Trauma teams in Pakistan is essential for enhancing collaboration and improving patient survival outcomes.